Alterations in microhabitat can impact litter decomposition by modifying the litter C/N ratio and regulating soil microbial activity - Li, Meiqi; Wang, Jianian; Li, Xiangyi (Frontiers in Plant Science, 2026)
IntroductionUnder extreme drought conditions, the mechanisms of litter decomposition and the associated microbial activities differ significantly from those in non-drought regions. These differences are primarily attributed to reduced precipitation, sparse vegetation cover, intense solar radiation, and unstable soil environments. However, it remains unclear how alterations in litter properties and soil microbial communities—induced by changes in the microenvironment under extreme drought—affect the processes of litter decomposition.MethodsTo address this issue, we selected two distinct habitat types, applied two sand-burial treatments (surface vs. 15 cm depth), and employed the litterbag method to investigate how variations in microenvironmental conditions influence litter decomposition via changes in litter quality and soil microbial communities.ResultsThe results indicated that in vegetated areas, sand burial enhanced nitrogen (N) release from litter by 16.56%, accelerated carbon (C) release by 13.13%, and significantly increased mass loss by 7.50%. Structural equation modeling further revealed that Actinobacteria and Ascomycota significantly promoted litter decomposition in vegetated areas by enhancing lignin degradation. In contrast, the higher decomposition rate of surface litter in non-vegetated areas (litter decomposition rate (k): 0.421 vs. 0.275) suggests that abiotic factors are more influential in driving decomposition on exposed sandy land. A 29.37% increase in lignin breakdown, likely due to photodegradation, may be the primary mechanism accelerating surface litter mass loss in these areas.DiscussionIn summary, modifications to the microenvironment influence litter decomposition by altering nutrient release and the composition of soil microbial communities, ultimately affecting ecosystem C and N cycling in arid environments.